Demographic Characteristics, Social Support, and Mental Health among Senior Citizens - Sharma, Tilak Prasad (Journal of Jayaprithvi Multiple Campus, 2025)
The main purpose of the study is to determine how demographic factors and social support affect older citizens' mental health. A survey of Nepalese elderly people shows that they are increasing in numbers at an alarming rate and most of them suffering from mental health problems. The effect of social support on elderly people’s psychological health in Chandragiri Municipality, Kathmandu Nepal, is a subject of focus in this study. In this study a cross-sectional study design was applied and the data were received from 120 respondents by using structured interviews. Research findings show that the availability of social support especially in the forms of emotional and instrumental support is vital in reducing loneliness depression and anxiety. Those individuals, who reported higher levels of perceived support, will exhibit better mental health. Mental health was significantly affected by rejection and poor home conditions according to keen findings thereby pointing towards important areas for intervention. The implications for practice from this study suggest the need to strengthen social support networks to bolster the elderly mental health, especially in rural contexts.